BROADBAND MICROSTRIP LOOP ANTENNAS - Yang, Jianming (My University, 1997)
This thesis involves the development of a new and compact microstrip loop antenna which combines high gain and broad bandwidth in an easy to fabricate structure. The antenna has many potential applications as its geometrical layout makes it easy to design linear and planar arrays. Practical antennas in the form of 1-element, 2-element, 4-element and 8-element were successfully constructed and tested at the frequency band of 940-956 MHz for a personal communication service (PCS) system. Experimental investigations were also carried out for applications in the band of 2-GHz wireless telecommunication systems. Instead of the traditionally used uniform current approach, the antenna’s radiation patterns are modeled in a more realistic fashion: a non-uniform current distribution approach. This approach yields formulas which can be conveniently used to predict the radiation patterns of the antenna and the antenna arrays. The theoretical component of the microstrip loop antenna is also presented in this thesis.
Keywords: Microstrip Loop Antenna; Bandwidth; Personal Communication Service; PCS; Current distribution; Dual-ring microstrip